2011
DOI: 10.1111/j.1744-6163.2010.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Addictions and Bariatric Surgery for Nurses in Recovery

Abstract: Evidence suggests that some individuals may require additional treatment, similar to those with pharmacological addictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Wiedemann et al also found that patients with a preoperative SUD history tended to use more types of substances than new-onset SUD patients. In another study examining 173 nurses who underwent bariatric surgery (Fogger & McGuinness, 2012), 68% (n=17) of them reported their problems initiated after surgery. Tedesco et al (2013) suggested that the prevalence of postoperative substance abuse among bariatric patients with a prior history was much higher than those without the history, although the difference was not significant (8.1% vs.1.5%, p= .234), which might be related to a small sample of postoperative substance abuse group (n=8, 6 with prior history and 2 without).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiedemann et al also found that patients with a preoperative SUD history tended to use more types of substances than new-onset SUD patients. In another study examining 173 nurses who underwent bariatric surgery (Fogger & McGuinness, 2012), 68% (n=17) of them reported their problems initiated after surgery. Tedesco et al (2013) suggested that the prevalence of postoperative substance abuse among bariatric patients with a prior history was much higher than those without the history, although the difference was not significant (8.1% vs.1.5%, p= .234), which might be related to a small sample of postoperative substance abuse group (n=8, 6 with prior history and 2 without).…”
Section: Resultsmentioning
confidence: 99%
“…tolerance or overdose). Adults in some occupations might be vulnerable to developing substance use problems, such as nurses, who have high levels of job stressors and access to substances at work (Fogger & McGuinness, 2012). Veterans are also at high risk of postoperative substance use due to their high prevalence of psychological and psychiatric problems (Adams et al, 2012; Tedesco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Roux-en-Y gastric bypass (RYGB) patients may be at risk for alcohol use disorders, particularly by the second postoperative year (King et al, 2012), and they may also encounter drug problems (Fogger & McGuinness, 2012;Saules et al, 2010). One study found that post-bariatric surgery patients are overrepresented in substance abuse detoxification/ 406 S. RESLAN ET AL. rehabilitation programs for alcohol and other drug use disorders.…”
Section: Introductionmentioning
confidence: 98%
“…Much of this literature has focused on the development of problems with alcohol use. Until recently, published empirical literature in this area has been quite limited, and generally has involved cross-sectional or retrospective studies with relatively small sample sizes (1316) , with several notable exceptions. Three recent prospective reports are of particular interest.…”
Section: Introductionmentioning
confidence: 99%